Influence of organic and inorganic nitrogen on the growth and yield of irrigated rice (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The objective of this research was to evaluate the impact of organic and inorganic sources of nitrogen (N) on growth dynamics, yield, N content, N uptake and agronomic efficiency (AE) of irrigated rice. Four  high-yielding boro (dry season irrigated) rice cultivars viz. BRRI dhan29, BRRI dhan59 Binadhan-8 and Binadhan-10 along with six N management combinations viz. Control (no N application), 140 kg N ha-1 from Prilled Urea (PU), 83 kg N ha-1 from Urea Super Granule (USG), 105 kg N ha-1 from PU + 3 t ha-1 Poultry manure, 112 kg N ha-1 from PU + 5 t ha-1 Cowdung and  77 kg N ha-1 from PU + 4 t ha-1 vermi compost were used in the study. The cultivar Binadhan-8 had a higher yield than all other cultivars because of the highest total dry matter (TDM), number of effective tillers hill-1, and number of grains panicle-1.Growth, TDM, yield, and AE were highest with 105 kg N ha-1 from PU + 3 t ha-1 Poultry manure application .The highest N uptake in grain and straw (120.1 kg ha-1 and 96.14 kg ha-1, respectively) was shown by rice cultivar Binadhan-8. In addition, significant relationships between N concentration and growth dynamics, TDM, N content, N uptake, and yield were observed. These results indicated that cultivars with the capacity to uptake more N can produce more yield and N application along with poultry manure could enhance growth, yield, AE. Therefore, the combined application of N sources in the form of PU + Poultry manure can produce good performances in terms of growth and yield of HYV rice under irrigated condition.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 9-23